Penerapan Tri Kaya Parisudha (Tkp) Dalam Praktik Profesi Akuntan Publik - Anam, Mohamad Khoirul; Adhitanaya, Komang (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to explore the application of Tri Kaya Parisudha (TKP) in the practice of public accounting profession. TKP, which consists of manacika (thinking well), wacika (speaking well), and kayika (doing good), is used to identify and interpret the reference attitude for upholding ethics that must be possessed by a public accountant (AP). This type of research is descriptive qualitative, which is used to reveal the meaning contained in TKP and actualized in the ethics of public accountants. The study findings reveal that manacika (thinking well), wacika (speaking well), and kayika (doing good) are consistent with the Public Accountants Code of Ethics (KEPAP). The application of TKP in the practice of public accounting profession is important to maintain professional ethics and standards. To apply it, AP must be consistent in thinking, speaking, and acting positively. By incorporating TKP values into the professional code of ethics, regulators can encourage ethical behavior and accountability among APs. Further research can continue this study by adding interviews with religious and cultural figures to dig deeper into the values of TKP.